PENGARUH SELF ASSESMENT SYSTEM DAN KETEPATAN PELAPORAN SPT TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BELAWAN - Rosanna Purba (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
This study aims to analyze the effect of self assessment system and the accuracy of SPT reporting on receipt of Value Added Tax (VAT) at the KPP Pratama Medan Belawan. Each self assessment system variable and the accuracy of SPT reporting will be tested and analyzed partially and simultaneously on receipt of VAT. The study sample was a Taxable Entrepreneur registered at the KPP Pratama Medan Belawan in the 2014-2016 period. The method of data collection uses library and field methods. The method used in this study is a quantitative approach, with a type of quantitative descriptive research. The statistical model used is a multiple linear regression model by SPSS program. The conclusion of this study is that partially the self assessment system variable significantly influences the receipt of VAT. Likewise the variable accuracy of SPT reporting also significantly influences the receipt of VAT. Based on the results of the simultaneous test, the self assessment system variable and the accuracy of the joint SPT reporting together have a significant effect on receipt of VAT.